Kazahsztán Afrika kapcsolatai: békeharcos vagy jó kereskedő? - Vasa, László (Afrika Tanulmányok / Hungarian Journal of African Studies, 2020)
Kazakhstan is a thirty-year-old state, which, along with its nation-building, has been ambitious in establishing its international relations. Balancing with the major and emerging powers, over the last ten years, priority has been given to building relations with the countries of the African continent, but this is by no means limited to bilateral relations; Kazakhstan is actively involved in the work of the African Union and is trying to mediate in conflicts. The question is, what are the interests of an oil-rich, vast but relatively low-populated, economically consolidated country, which is not one of the largest economies in the world in its relations with African countries? In this article, I would like to explore the background and connections of this with the hypothesis that the interests of Kazakhstan in the region are not necessarily economic, but rather aim to increase its international recognition and reputation.